2021
DOI: 10.1037/xhp0000918
|View full text |Cite
|
Sign up to set email alerts
|

Spatial cueing effects are not what we thought: On the timing of attentional deployment.

Abstract: Extensive research has shown that objects that are salient or match our task goals are most likely to capture our attention. But are we at the mercy of the constant changes occurring in our environment, and automatically move our attention to the ever-changing location with the highest priority? Or do we wait for clues that the appropriate moment has arrived to deploy our attention? We addressed this hitherto neglected issue in three experiments. Using a spatial-cuing paradigm, we examined whether attention is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Similar to older interpretations of validity effects as reflecting processes in the target displays (cf. Shiu & Pashler, 1994), researchers recently suggested that some validity effects could also reflect processes following the target’s onset, during target search, and dependent on the difficulty of target search (Yaron & Lamy, 2021). Thus, in line with the priority-accumulation framework by Yaron and Lamy (2021), the spatial de-prioritization induced by our negative features might not solely reflect cue-elicited suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to older interpretations of validity effects as reflecting processes in the target displays (cf. Shiu & Pashler, 1994), researchers recently suggested that some validity effects could also reflect processes following the target’s onset, during target search, and dependent on the difficulty of target search (Yaron & Lamy, 2021). Thus, in line with the priority-accumulation framework by Yaron and Lamy (2021), the spatial de-prioritization induced by our negative features might not solely reflect cue-elicited suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the peak on this map depends on the relative strengths of the different guiding factors at any given moment. Note that while this peak is often thought to determine where attention will be shifted next, other suggestions have been put forward (see, e.g., Moran et al, 2013, for a probabilistic relation between priority and attention allocations; Yaron & Lamy, 2021 for the idea that contextual information constrains when the next shift of attention to the peak on the priority map is triggered).…”
Section: Guidancementioning
confidence: 99%
“…Elucidating what type of contextual information may influence the probability that attention is deployed at any given moment is an important avenue for future research. In a previous study (Yaron & Lamy, 2021), we showed that participants waited for the search display to deploy their attention when the cue and search displays were easy to discriminate, but not when these could be distinguished only by temporal order (i.e., the search display was similar to the cue display but always came last). This finding suggests that to allocate their attention, participants were not able to rely on temporal information alone (see Pomper et al, 2023 for a similar conclusion) and instead relied on characteristics of the search display (the critical aspects of which are yet to be identified).…”
Section: Discussionmentioning
confidence: 85%
“…According to PAF, our visual selection system enjoys more degrees of freedom than is implied by online-prioritization theories, as to when we deploy our attention to the highest-priority location (Darnell & Lamy, 2022; Gabbay et al, 2019; D. Lamy et al, 2018; Yaron & Lamy, 2021). This model differs from online-prioritization models by two main hypotheses.…”
Section: The Role Of Contextual Information In the Timing Of Attentio...mentioning
confidence: 99%
See 1 more Smart Citation